«INTEGRATED FORENSIC BALLISTICS/MEDICAL INVESTIGATIONS»: NEW ADDITION TO THE CURRICULUM IN FORENSIC SCIENCE CONCENTRATIONS 8.1 AND 8.2 - M. Sonis; I. Gedygushev (Теория и практика судебной экспертизы)
.